2020
DOI: 10.2147/jmdh.s282776
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of Undergraduate Pharmacy Students’ Attitude Towards Pharmaceutical Care in Pakistan: Practice Implications</p>

Abstract: Background and Purpose Over the past few decades, the focus of pharmacy practice has been shifted from the classical role of drug dispenser to pharmacotherapy expert. Pharmacists now are more often involved in the patient care process by addressing the drug-related needs of the patients and this patient-centered approach is known as pharmaceutical care (PC). The present study was conducted to assess the attitude of pharmacy undergraduate students toward PC and various contributing factors that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Most pharmacy students were self-motivated to undertake pharmacy education, and less than twenty percent were females; this was lower than reported studies in Kuwait, Malaysia, Nepal, and UEA. 14 , 17 , 19 , 25 Furthermore, their preferred career after graduation was in pharmaceutical marketing, followed by the pharmaceutical industry. The availability of 500 foreign pharmaceutical companies and more than 13,000 brand medicines registered in this country could have influenced their choice of pharmaceutical marketing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most pharmacy students were self-motivated to undertake pharmacy education, and less than twenty percent were females; this was lower than reported studies in Kuwait, Malaysia, Nepal, and UEA. 14 , 17 , 19 , 25 Furthermore, their preferred career after graduation was in pharmaceutical marketing, followed by the pharmaceutical industry. The availability of 500 foreign pharmaceutical companies and more than 13,000 brand medicines registered in this country could have influenced their choice of pharmaceutical marketing.…”
Section: Discussionmentioning
confidence: 99%
“… 14–18 , 18 , 19 This instrument was selected since it has been widely used around the world, such as in USA, 13 Saudi Arabia, 16 Kuwait, 17 Qatar, 18 UAE, 19 Cuba, 15 Malaysia, 24 and Pakistan. 25 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive attitude towards pharmaceutical care in mental illness was observed among the study participants. A previous study also reported a positive attitude towards the practice of pharmaceutical care among pharmacy students in Qatar (El Hajj et al, 2014) and Pakistan (Hussaine et al, 2020). A positive attitude towards pharmaceutical care services may likely result in the enhanced practice of the model, resulting in improved patient outcomes and reduced cost of treatment.…”
Section: Discussionmentioning
confidence: 86%